Efficacy of Oral Alitretinoin in Treatment of Mycosis Fungoides Palmaris et Plantaris - Sun Mun Jeong; Seol Hwa Seong; Min Soo Jang; Kee Suck Suh; Jong Bin Park (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)